1. No
2. No
3. Yes
4. No, it’s actually 24j -36
There are 151,200 possible combinations. If you'd like an explanation of my answer, please let me know.
Answer:
-1
Step-by-step explanation:
m = -7 / 7 = -1 / 1 = -1
Answer:
The product of 2x + y and 5x – y + 3 is 10x^2+ 3xy + 6x - y^2 + 3y
Step-by-step explanation:
The product of the two expressions can be expressed mathematically as;
(2x +y) (5x -y +3)
To obtain the product of these expressions, we simply expand the brackets as follows;
2x(5x -y +3) + y(5x -y +3)
= 10x^2 - 2xy + 6x + 5xy - y^2 + 3y
= 10x^2- 2xy + 5xy + 6x - y^2 + 3y
= 10x^2+ 3xy + 6x - y^2 + 3y
The product of 2x + y and 5x – y + 3 is thus 10x^2+ 3xy + 6x - y^2 + 3y